The effects of intermittent task parameters on muscle fatigue development during submaximal dynamic exertions - King, Josephine Claire (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2018)
The negative effects of localised muscle fatigue on accidents, injuries and poor work performance are well known, as is the realisation that modifying task characteristics can minimise fatigue development. A large amount of literature has investigated the effects of task-dependent factors on localised muscle fatigue, most studies have focussed on prolonged or intermittent static (isometric) exertions. Few studies have investigated muscle fatigue development during more complex tasks, namely those which resemble common work activities and which tend to be intermittent and dynamic in nature. More specifically, the interactions between the main intermittent parameters - duty cycle, force level, and cycle time - during dynamic exertions are poorly understood. The purpose of this study was to investigate the effects of cycle time and combinations of duty cycles and force levels on the development of muscle fatigue during submaximal dynamic exertions while the overall mean muscle load was kept constant. A two-factorial repeated-measures experiment was developed for this study. Nine experimental conditions, each lasting 16 minutes, aimed at inducing muscle fatigue in the middle deltoid muscle via intermittent dynamic shoulder abduction and adduction motions at three cycle times (30, 60, and 120 seconds) and three combinations of duty cycles and force levels. The percentage of muscle activation during one cycle (i.e. the duty cycle) varied depending on the exertion intensity (force level) so that the overall mean muscle load remained consistent throughout all experimental conditions, namely at 20% of maximum force exertion. As a result, the three duty cycle/force level combinations were: 0.8/25% of maximum voluntary force (MVF), 0.5/40%MVF, and 0.4/50%MVF. Muscle fatigue development was inferred by changes in peak torque, total work, average power, local Ratings of Perceived Exertion (RPE), and surface electromyographical (EMG) activity (time domain and frequency domain).Two-factorial analyses of variance with Tukey post-hoc tests were used to identify significant condition effects at p<0.05. All dependent measures showed that muscle fatigue was induced by the 16-minute fatigue protocol. Peak torque, total work, average power, and EMG percentage of maximum showed that cycle time and the duty cycle/force level combination had no effect on the development of muscle fatigue, whereas the measures evaluated during the 16-minute fatigue protocol did. The cycle time of 120 seconds induced the greatest change in six of the eight variables, while the duty cycle/force level combination (0.8/25%) also resulted in the greatest effect in six of the measures. Fatigue was also found to be dependent on the interaction of cycle time and duty cycle/force level combination. The conclusion draws from this study is that shorter cycles and activities with short activation periods, and proportionally longer rest breaks result in the lowest fatigue developments.
Keywords: Muscles -- Physiology; Muscles -- Wounds and injuries; Fatigue; Human engineering; Occupational diseases